The evaluation of the II Pillar pension’s funds: an integrated approach using multi-criteria decision methods - Novickytė, Lina; Rabikauskaitė, Viktorija (Business: Theory and Practice, 2017)
Lithuania has had a significant reform path in the last twenty-five years like other communist bloc countries during the intense changes in the world. Changes and transformations took place in various areas including social security system. Since 2004 have been significant developments legalizing the three-pillar old age pension system supported by the World Bank. Currently, the pension funds operating more than ten years and their assessment still have not stopped being the centre of numerous discussions. There are ongoing discussions about the fund performances’ benefit, efficiency and its evaluation. Therefore, this paper investigates the funds’ valuation problem by testing II pillar pension’s funds in Lithuania. We use the multi-criteria methods with two scenarios: first we estimate II pillar pension’s funds by applying a return (as well as the added value) and the risk indicators; second we include only the most popular derivative indicators: Sharpe, Treynor and Jensen’s alpha ratios. Our results indicate that based on the second scenario methodology is more precise evaluated II pillar pensions funds’ performance, but funds evaluation model based on multi-criteria assessment is more appropriate for larger funds groups. However, in order to assess the performance of the funds and compare them with each other it is important not only use the mathematical methods but also to maintain a holistic approach which allows to integrate micro and macro environmental factors into the funds’ assessment.